The Influence of Digital Pocket Books on Parents' Knowledge of Early Childhood Sexual Education - Elisabeth Fransisca Saragi Sitio; Kartika Ananda; Rahmah Dwi Sistiarini (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to address parents’ need for clear, practical, and easy-to-understand guidance in introducing early childhood sexual education. In response to the increasing urgency of preventing sexual violence against children, this research examines the influence and effectiveness of a digital pocketbook as an educational medium to improve parents’ knowledge of early childhood sexual education. The study employed a quantitative research approach using a one–group pretest–posttest design. The research sample consisted of 14 parents of students enrolled at Pembina State Kindergarten, located in Bukit Batu District, Palangka Raya City, Central Kalimantan. Data were collected through pretest and posttest instruments and a questionnaire to capture parents’ responses to the use of the digital pocketbook. The analysis results demonstrate a significant increase in parents’ knowledge after the intervention, indicating that the digital pocketbook had a positive influence and was an effective learning tool. In addition, parents expressed favorable responses regarding the clarity, accessibility, and usefulness of the digital pocketbook in supporting their understanding of early childhood sexual education. These findings highlight the potential of digital educational media as a practical solution for parental education. The results of this study are highly relevant. They can serve as a reference for parents, educators, and early childhood education stakeholders in strengthening preventive efforts against sexual violence involving young children.